The E-MODUL HYPERCONTENT UNTUK MENINGKATKAN BERPIKIR KRITIS DAN MENYUSUN LAPORAN ASESMEN PERKEMBANGAN ANAK - Asmawati, Luluk Asmawati; Rusijono; Mariono, Andi (UNIB Press, 2026)
The purpose of the hypercontent e-module research was to improve critical thinking skills and the ability to compile assessment reports. The research method used the ADDIE model. The research subjects were 24 students. Data collection techniques used questionnaires and observations. Data analysis techniques used descriptive statistical data. The results of the study: (1) the validity results carried out by learning design experts were 97% feasibility percentage, material experts were 100% feasibility percentage, and media experts were 100%. The hypercontent e-module had a very high feasibility percentage of 95%-100%; (2) critical thinking results of the pretest t-test, obtained a Sig. (2-tailed) value of 0.190 > 0.05, which indicates that there was no significant difference between the critical thinking abilities of students in the experimental class and the control class before being given treatment. This finding indicates that the initial critical thinking abilities of students in both classes are at a relatively similar level; (3) compiling a child development assessment report, results of the pretest t-test, obtained a Sig. (2-tailed) value of 0.620 > 0.05, which indicates that there was no significant difference between the abilities of students in compiling a child development assessment report in the experimental class and the control class before being given treatment. Conclusion: The hypercontent e-module for developmental assessment was a very suitable, relevant, and effective medium for improving critical thinking and the ability to compile child developmental assessments.